2020
DOI: 10.7566/jpsj.89.051015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Approach to Physicochemical Hydrogen Processes on Cosmic Ice Dust

Abstract: Hydrogen is the most abundant element in the universe, and thus atomic and molecular hydrogen play important roles in chemical evolution in space. In particular, the physicochemical processes of hydrogen on cosmic dust, such as the diffusion of H atoms and nuclear spin conversion of H2 molecules at low temperatures, are recognized to significantly influence the subsequent chemical evolution. However, it is not easy to track the hydrogen on the surface by conventional experiments. We have recently succeeded in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Moreover, we found that H 2 was formed efficiently on the DLC even at 20 K, which is higher than the threshold for H 2 formation on ASW. However, the formation at 20…”
Section: Hydrogen Reactions On Icy Grainsmentioning
confidence: 99%
“…Moreover, we found that H 2 was formed efficiently on the DLC even at 20 K, which is higher than the threshold for H 2 formation on ASW. However, the formation at 20…”
Section: Hydrogen Reactions On Icy Grainsmentioning
confidence: 99%
“…The REMPI (resonance-enhanced multiphoton ionization [66]) method was initiated by K. Fukutani and its group at Tokyo University to study the H 2 conversion on silver samples in 2003 [41,42]. Later, in 2010, Watanabe et al, Sugimoto and Fukutani observed the o-p conversion of hydrogen adsorbed on amorphous solid water ice (ASW) by a combination of photo-stimulated desorption and "REMPI" methods [65,66,[77][78][79][80][81][82]. Later on, they were able to detect hydrogen conversion on other cosmic dust analogues: polycrystalline ice (PCI), pure solid carbon monoxide, and diamond-like carbon.…”
Section: H 2 Adsorbed On Solid Watermentioning
confidence: 99%
“…The physicochemical processes of hydrogen on cosmic dust, such as the diffusion of H atoms and nuclear spin conversion of H 2 molecules at low temperatures, have a significant influence on the subsequent chemical evolution in space [50,[77][78][79][80][81][82]. The birthplace of stars and planets, namely, the interstellar cloud consisting of gaseous species and cosmic silicate dust, are the starting point of chemical evolution in space, where most of the relatively light elements, such as hydrogen, carbon, oxygen, and nitrogen, first exist as atoms.…”
Section: H 2 Adsorbed On Solid Watermentioning
confidence: 99%
“…This PSD-REMPI method has been successfully applied for detecting atomic and molecular hydrogen on analogues of astronomical dust surfaces, 17−22 and the experimental outcomes are summarized in a recent review paper. 23 In this account, we introduce the application of the PSD-REMPI method for the detection of OH radicals on ASW surfaces (section 2). 1 In section 3, the electrondriven chemistry of OH radicals on ASW, as demonstrated from the observation of a negative charge current, will be overviewed, 2,3 and a future outlook will be given in section 4.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group developed a new method to sensitively detect surface adsorbates with a combination of photostimulated desorption (PSD) and resonance-enhanced multiphoton ionization (REMPI) techniques. This PSD-REMPI method has been successfully applied for detecting atomic and molecular hydrogen on analogues of astronomical dust surfaces, and the experimental outcomes are summarized in a recent review paper . In this account, we introduce the application of the PSD-REMPI method for the detection of OH radicals on ASW surfaces (section ).…”
Section: Introductionmentioning
confidence: 99%